2019
DOI: 10.1098/rsif.2019.0259
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behaviours of the bone–implant interface: a review

Abstract: In recent decades, cementless implants have been widely used in clinical practice to replace missing organs, to replace damaged or missing bone tissue or to restore joint functionality. However, there remain risks of failure which may have dramatic consequences. The success of an implant depends on its stability, which is determined by the biomechanical properties of the bone–implant interface (BII). The aim of this review article is to provide more insight on the current state of the art concerning the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 182 publications
0
94
0
1
Order By: Relevance
“…This may confirm the existence of differences in the osseointegration of porous implants with osteoporosis bone. An important role in achieving good long-term results during acetabular reconstruction is influenced by both a correct choice of implant and the bone quality in the periprosthetic acetabular area [10,38]. It has been shown that in the osteoporotic bone, the rate of migration of uncemented acetabular cups is elevated [2].…”
Section: Discussionmentioning
confidence: 99%
“…This may confirm the existence of differences in the osseointegration of porous implants with osteoporosis bone. An important role in achieving good long-term results during acetabular reconstruction is influenced by both a correct choice of implant and the bone quality in the periprosthetic acetabular area [10,38]. It has been shown that in the osteoporotic bone, the rate of migration of uncemented acetabular cups is elevated [2].…”
Section: Discussionmentioning
confidence: 99%
“…This may con rm the existence of differences in the osseointegration of porous implants with osteoporosis bone. An important role in achieving good long-term results during acetabular reconstruction is in uenced by both a correct choice of implant and the bone quality in the periprosthetic acetabular area [10,38]. It has been shown that in osteoporotic bone the rate of migration of uncemented acetabular cups is elevated [2].…”
Section: Discussionmentioning
confidence: 99%
“…This may con rm the existence of differences in the osseointegration of porous implants with osteoporosis bone. An important role in achieving good long-term results during acetabular reconstruction is in uenced by both a correct choice of implant and the bone quality in the periprosthetic acetabular area [10,37]. It has been shown that in osteoporotic bone the rate of migration of uncemented acetabular cups is elevated [2].…”
Section: Discussionmentioning
confidence: 99%